PENGARUH PEMBERIAN JUS ALPUKAT TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DI KELURAHAN DENAI KECAMATAN DENAI KOTA MEDAN TAHUN 2022 - Ariescha, Putri Ayu Yessy (Jurnal Inovasi Kesehatan Masyarakat, 2024)
Hypertension in pregnancy is hypertension described by circulatory strain 140/90 mmHg following 20 weeks of growth, joined by proteinuria 300 mg/24 hours. Hypertension in pregnancy is a significant reason for maternal and fetal dismalness and mortality. Hypertension happens in 5-10% of pregnancies. 2 different ways of treating hypertension are pharmacological and non-pharmacological. This examination was directed in Denai Town, Medan City from February to June 2022. This sort of examination is a semi explore utilizing a one gathering pretest-posttest. Still up in the air in this study were pregnant ladies with hypertension who were kept in Denai Town. The quantity of accessible examples is 16 examples taken by purposive inspecting from the populace. The consequences of the bivariate examination of the impact of giving avocado juice on diminishing circulatory strain got p-upsides of systolic (0.000) and diastolic (0.000). From the aftereffects of the bivariate examination with p-esteem < (0.05), can be reasoned that there is the arrangement of avocado juice on decreasing circulatory strain of pregnant ladies in Denai Town, Medan Denai Area, Medan City in 2022. It is prescribed for pregnant ladies to exploit non-pharmacological treatments, for example, utilization of avocado juice to bring down circulatory strain and lessen the utilization of clinical medications that can cause incidental effects.